Commitment to sustainability in supplier companies in the mining sector: analysis of corporate missions in San Juan, Argentina - Coria Augusto, Cesar Javier (2025)
This study examines how supplier companies in the mining sector in San Juan, Argentina, integrate sustainability principles into their corporate missions, using discourse analysis as the main methodology. Through a sample of 29 companies with active websites, patterns and trends were identified in the representation of the economic, social, and environmental dimensions of sustainable development. The findings reveal a marked predominance of the economic dimension, reflected in 100% of the analyzed missions, while the social and environmental dimensions are present in 44.83% and 34.48% of cases, respectively. This imbalance suggests a partial view of sustainability, which could limit the positive impact of these companies on their communities and the natural environment. The study highlights the importance of strengthening the integration of the three pillars of sustainability into the communication and operational strategies of supplier companies. Furthermore, it underscores the need for awareness programs, training, and regulatory policies that promote responsible practices. This work contributes to academic knowledge by addressing an underexplored aspect in the literature and provides practical recommendations to enhance sustainability in the mining value chain, aligning with global standards such as the Sustainable Development Goals (SDGs).